Developing Strategies to Improve Business Model of Online Laundry Marketplace Startup - Taqyya Naufinda Asnin; Yudha Prambudia; Rosad Ma’ali El Hadi (International Journal of Innovation in Enterprise System, 2021)
The Infineeds is a startup engaged in online laundry marketplace services for households. The currentonline marketplace business can be considered as a fairly competitive business, especially forInfineeds which is a new business or startup. Therefore, it is important for Infineeds to have a wellprepared sustainable business model. The Business Model Canvas was used to analyze Infineeds'business model. With a Strengths, Weaknesses, Opportunities, Threats analysis approach, alternativebusiness development strategies are obtained that are in accordance with the company's internal andexternal environmental conditions. The weighting using Quantitative Strategic Planning Matrix isdone to get alternative priorities for business development strategies. The priority alternatives are thenincluded in the Business Model Canvas as a new component. The results of the analysis show thatInfineeds is in a growth-oriented strategy position, which is to take advantage of internal strengths totake advantage of as many opportunities as possible with the highest alternative development strategyis the strategy to using Search Engine Optimization with Total Attractiveness Score is 6.62 as well asthe development of a business model canvas on the components of channels, key activities, and keypartners